KISS1 protein expression is associated with worse prognosis in osteosarcoma patients: a long-term follow-up study - Chen, Hui; Chen, Peisheng; Lin, Fengfei; Chen, Shunyou; Lin, Jianhua (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: A long-term follow-up study was used to analyze the relationship between KISS1/GPR54 protein expression and the clinical prognosis of osteosarcoma (OS) patients. Methods: Forty-four paraffin-embedded OS samples conserved during the period from 2005 to 2009 were studied. Information about gender, age, pathological type, surgical stage, and clinical outcome was collected from the medical records. Results: This study included 25 males (56.81%) and 19 females (43.19%) with a median age at diagnosis of 18 years (range, 12–74 years). The follow-up duration ranged from 97 to 162 (121.36±15.46) months. The overall survival and metastatic rates were 43.18% and 65.91% respectively. For KISS1, the rate of distal metastasis and mortality in positive expression patients were 85.00% (17/20) and 75.00% (15/20) respectively, and 50.00% (12/24) and 41.67% (10/24) in negative expression patients respectively. In terms of survival time, KISS1 positive and negative patients were 55.35±14.29 and 97.46±13.06 months, respectively. P0.05 in these three aspects. Conclusions: Expression of KISS1 protein correlated with higher distal metastasis and shorter survival time in OS patients after an average of 10.11 years of follow-up. GPR54 protein did not affect the prognosis when expressed alone.